2004
DOI: 10.1111/j.1600-0722.2004.00115.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and sealing properties of four classes of endodontic sealers evaluated by succinic dehydrogenase activity and confocal laser scanning microscopy

Abstract: The objectives of this study were to evaluate the cytotoxicity and sealing properties of four classes of endodontic sealers (PCS/Kerr, RoekoSeal/Roeko, TopSeal/Dentsply, and EndoREZ/Ultradent). For cytotoxicity testing (MTT method), the materials were either placed immediately in contact with cultured cells or 24 h after setting, then evaluated at three subsequent time points (24 h, 48 h, or 1 wk). For the leakage study, extracted human roots were obturated with acrylic cones and sealers and immersed for 48 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
78
2
12

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(114 citation statements)
references
References 29 publications
22
78
2
12
Order By: Relevance
“…An example is the MTT assay. In this assay, the yellow MTT salt, which has a ring-shaped molecular structure, is absorbed by cells and cleaved by an enzyme inside the mitochondria, giving origin to a product named formazan in the form of purple-colored non-soluble crystals (12,18,19). To achieve this result, the identification of the color intensity of the solution is done by an ELISA spectrophotometer, with a high accurate reading in cytotoxicity studies (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An example is the MTT assay. In this assay, the yellow MTT salt, which has a ring-shaped molecular structure, is absorbed by cells and cleaved by an enzyme inside the mitochondria, giving origin to a product named formazan in the form of purple-colored non-soluble crystals (12,18,19). To achieve this result, the identification of the color intensity of the solution is done by an ELISA spectrophotometer, with a high accurate reading in cytotoxicity studies (18).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is a low-cost procedure that yields results within 48 h (12,13,18,19), and is therefore the most commonly used procedure for determining the cytotoxicity of different types of materials (20). Due to these characteristics and the endorsement by some authors (13,15,(21)(22)(23)(24)(25), this assay was used in this study for assessing the cytotoxicity of all the six endodontic sealers.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are three recommended tests for the biological evaluation and acceptance of endodontic materials: a primary test or cell culture test which provides a general profile of toxicity for the material (level 1), a secondary test or material implantation test which evaluates its local toxicity in experimental animals (level 2) and usage test in which the material is used in the endodontic treatment of teeth in experimental animals (level 3). In cell culture tests, several studies have been performed and all have found different degrees of cytotoxicity for various sealers [1,2,3]. Bouillaguet et al (2004) [1] evaluated cytotoxicity of several sealers at cell culture and reported that the cytotoxicity of sealers increases with time from 24hr to 1 week and most sealers are potentially, cytotoxic specially when they are mixed freshly .…”
Section: Introductionmentioning
confidence: 99%
“…In cell culture tests, several studies have been performed and all have found different degrees of cytotoxicity for various sealers [1,2,3]. Bouillaguet et al (2004) [1] evaluated cytotoxicity of several sealers at cell culture and reported that the cytotoxicity of sealers increases with time from 24hr to 1 week and most sealers are potentially, cytotoxic specially when they are mixed freshly . Huangetal [3] demonstrated that Diaket exhibit not only in vitro dose dependent cytotoxicity but also genotoxicity and that cytotoxicity of ZOE was detectable as early as 1hr after mixing and remained at a high level until 5 week.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the biocompatibility of all dental materials that could potentially come in contact with tissues should be investigated (1). This property is of special significance for endodontic materials (3,4) because sealants may cause different reactions in the dental pulp (4)(5)(6)(7). Subcutaneous tissue reaction is one of the in vivo biocompatibility tests that have been used for evaluating several new materials (2,(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%